Peran Pendidikan Islam dalam Menghadapi Krisis Moral dan Etika Sosial - Ahmad Syukri; Sri Wahyuni Sihombing; Budiman Budiman; Ifnaldi Ifnaldi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to study the role of Islamic Education in facing the moral and social ethical crisis. The method used is a literature review, which analyzes sources or data from scientific journals on topics relevant to the research. The research results show that Islamic education can provide an example for someone to speak and behave according to religious demands (Al-Qur'an and Sunnah) to prevent a moral and social-ethical crisis. In conclusion, Islamic education can solve the moral, social, and ethical crises. In conclusion, implementing and strengthening Islamic Education can solve the problem of moral, social, and ethical crises. Islamic education can play a role in controlling attitudes, reminding oneself, and preventing oneself from detrimental actions Keywords: Islamic Education, Morals, Social Ethics